Multidimensional resonant nonlinear spectroscopy with coherent broadband x-ray pulses. (16th June 2016) - Bennett, Kochise; Zhang, Yu; Kowalewski, Markus; Hua, Weijie; Mukamel, Shaul
Abstract: New x-ray free electron laser (XFEL) and high harmonic generation (HHG) light sources are capable of generating short and intense pulses that make x-ray nonlinear spectroscopy possible. Multidimensional spectroscopic techniques, which have long been used in the nuclear magnetic resonance, infrared, and optical regimes to probe the electronic structure and nuclear dynamics of molecules by sequences of short pulses with variable delays, can thus be extended to the attosecond x-ray regime. This opens up the possibility of probing core-electronic structure and couplings, the real-time tracking of impulsively created valence-electronic wavepackets and electronic coherences, and monitoring ultrafast processes such as nonadiabatic electron-nuclear dynamics near conical-intersection crossings. We survey various possible types of multidimensional x-ray spectroscopy techniques and demonstrate the novel information they can provide about molecules.